Clinical, Endoscopic, and Histologic Characteristics of Patients with Solitary Rectal Ulcer Syndrome at a Tertiary Care Center - Shafiq, Syed (Journal of Digestive Endoscopy, 2023)
Objective Solitary rectal ulcer syndrome (SRUS) is a chronic disorder of defecation presenting with bleed per rectum, mucorrhea, tenesmus, perianal discomfort, etc. We aim to report clinical, endoscopic, and histologic features of SRUS in patients who underwent either colonoscopy or sigmoidoscopy at our center.Materials and Methods We performed retrospective analysis of all patients diagnosed with SRUS on endoscopy and confirmed by histopathologic examination at our center between January 2010 and June 2022. Data retrieved included demographic details, clinical features along with endoscopic, and histopathological findings of SRUS patients.Results The study included 132 patients with SRUS with mean (± standard deviation) age of 45 (± 20.6) years and male to female ratio of 1.5:1. While most of the patients presented with a combination of symptoms, the most common clinical presentation was bleeding per rectum (82%). Rectal ulcers, either single or multiple, were the predominant findings on endoscopy followed by polypoidal lesions. Histology showed fibromuscular obliteration and crypt distortion in all patients. Biofeedback training, lifestyle changes, and sucralfate enema were successful in about 87% of the patients at the end of 6 weeks and about 76% at the end of 12 weeks with surgery for rectal prolapse being performed in two of our patients.Conclusion SRUS presents with a myriad of symptoms and requires a high index of suspicion by the treating physician(s). While the most common presenting symptom in our study was rectal bleed rectal bleed; ulcers, either solitary or multiple, ulcers, either solitary or multiple, were the commonest endoscopy findings. Endoscopic findings along with histopathology confirm the diagnosis.
Keywords: bleeding; constipation; mucorrhea; rectal ulcer; tenesmus